Bibliometrics Analysis of the Research Status and Trends of the Association Between Depression and Insulin From 2010 to 2020 - Zou, Xiaohan; Sun, Yuan (Frontiers in Psychiatry, 2021)
Depression is one of the common mental illnesses. Because it is an important complication of diabetes, its association with changes in insulin levels and insulin resistance, the causative factors of diabetes, has attracted widespread attention. However, the association between insulin and depression has not been systematically studied through bibliometric and visual analysis. This study is based on 3131 publications of Web of Science to identify the current research status and research trends in this field. The results show that since 2010, the number of publications has been growing rapidly. Cooperative network analysis shows that the United States, the University of Toronto and Roger S Mcintyre are the most influential countries, research institutes and scholars respectively. Insulin resistance, obesity and metabolic syndrome are hot topics in this field. Analysis of keywords and references reveals that “sex hormones”, is new research area that constantly emerging. As far as we know, this study is the first one to visualize the association between depression and insulin and predict potential future research trends through bibliometric and visual analysis.